Biofilm-based Healthcare-associated Infections : Volume II - Donelli, Gianfranco (Advances in Experimental Medicine and Biology, 2015)
The aim of this book is to provide readers with a wide overview of the main healthcare-associated infections caused by bacteria and fungi able to grow as biofilm. The recently acquired knowledge on the pivotal role played by biofilm-growing microorganisms in healthcare-related infections has given a new dynamic to detection, prevention and treatment of these infections in patients admitted to both acute care hospitals and long-term care facilities. Clinicians, hygienists and microbiologists will be updated by leading scientists on the state-of-art of biofilm-based infections and on the most innovative strategies for prevention and treatment of these infections, often caused by emerging multidrug-resistant biofilm-growing microorganisms.